Question

# If the given expression $y=\dfrac{1-{{x}^{4}}}{1+{{x}^{4}}}$, then $\dfrac{dy}{dx}.\dfrac{dx}{dy}$ is equal to(a) $1$ (b) $xy$ (c) Does not exist (d) $\dfrac{x+y}{xy}$

Hint: First find derivative with respect to $'x'$ and then derivative with respect to $'y'$ . Multiply both to get the result.

The given expression is $y=\dfrac{1-{{x}^{4}}}{1+{{x}^{4}}}$.
First, we shall find $\dfrac{dy}{dx}$.
According to the quotient rule,
$\dfrac{d}{dx}\left( \dfrac{u}{v} \right)=\dfrac{v\dfrac{d}{dx}(u)-u\dfrac{d}{dx}(v)}{{{v}^{2}}}$
By applying this rule to given function, we get
$\dfrac{dy}{dx}=\dfrac{d}{dx}\left[ \dfrac{1-{{x}^{4}}}{1+{{x}^{4}}} \right]$
\begin{align} & \dfrac{dy}{dx}=\dfrac{(1+{{x}^{4}})\dfrac{d}{dx}(1-{{x}^{4}})-(1-{{x}^{4}})\dfrac{d}{dx}(1+{{x}^{4}})}{{{(1+{{x}^{4}})}^{2}}} \\ & \dfrac{dy}{dx}=\dfrac{(1+{{x}^{4}})(0-4{{x}^{3}})-(1-{{x}^{4}})(0+4{{x}^{3}})}{{{(1+{{x}^{4}})}^{2}}} \\ & \dfrac{dy}{dx}=\dfrac{(1+{{x}^{4}})(-4{{x}^{3}})-(1-{{x}^{4}})4{{x}^{3}}}{{{(1+{{x}^{4}})}^{2}}} \\ \end{align}
By taking â€˜$-4{{x}^{3}}$ â€™ common in the numerator, we get
\begin{align} & \dfrac{dy}{dx}=\dfrac{-4x{}^{3}[(1+{{x}^{4}})+(1-{{x}^{4}})]}{{{(1+{{x}^{4}})}^{2}}} \\ & \dfrac{dy}{dx}=\dfrac{-4{{x}^{3}}(2)}{{{(1+{{x}^{4}})}^{2}}} \\ \end{align}
$\dfrac{dy}{dx}=\dfrac{-8{{x}^{3}}}{{{(1+{{x}^{4}})}^{2}}}..........(i)$
Now, we will find $\dfrac{dx}{dy}$ for a given function.
As, $y=\dfrac{1-{{x}^{4}}}{1+{{x}^{4}}}$
By applying componendo and dividendo rule, we have
$\dfrac{y-1}{y+1}=\dfrac{(1-{{x}^{4}})-(1+{{x}^{4}})}{(1-{{x}^{4}})+(1+{{x}^{4}})}$
$\Rightarrow \dfrac{y-1}{y+1}=\dfrac{1-{{x}^{4}}-1-{{x}^{4}}}{1-{{x}^{4}}+1+{{x}^{4}}}$
Cancelling the like terms, we have
\begin{align} & \Rightarrow \dfrac{y-1}{y+1}=\dfrac{-2{{x}^{4}}}{2} \\ & \Rightarrow \dfrac{y-1}{y+1}=-{{x}^{4}} \\ & \Rightarrow {{x}^{4}}=\dfrac{-(y-1)}{y+1} \\ & \Rightarrow {{x}^{4}}=\dfrac{1-y}{1+y} \\ \end{align}
Now, by taking derivative of with respect to y, we have
$\dfrac{d({{x}^{4}})}{dy}=\dfrac{d}{dy}\left[ \dfrac{1-y}{1+y} \right]$
Again, by applying the quotient rule, we have
$4{{x}^{3}}\dfrac{dx}{dy}=\dfrac{(1+y)\dfrac{d}{dy}(1-y)-(1-y)\dfrac{d}{dy}(1+y)}{{{(1+y)}^{2}}}$
\begin{align} & 4{{x}^{3}}\dfrac{dx}{dy}=\dfrac{(1+y)(0-1)-(1-y)(0+1)}{{{(1+y)}^{2}}} \\ & \Rightarrow 4{{x}^{3}}\dfrac{dx}{dy}=\dfrac{(1+y)(-1)-(1-y)(1)}{{{(1+y)}^{2}}} \\ & \Rightarrow 4{{x}^{3}}\dfrac{dx}{dy}=\dfrac{-1-y-1+y}{{{(1+y)}^{2}}} \\ \end{align}
$4{{x}^{3}}\dfrac{dx}{dy}=\dfrac{-2}{{{(1+y)}^{2}}}$
Dividing throughout by â€˜2â€™, we get
$\Rightarrow \dfrac{dx}{dy}=\dfrac{-1}{2{{x}^{3}}{{(1+y)}^{2}}}.........(ii)$
Now as we have $y=\dfrac{1-{{x}^{4}}}{1+{{x}^{4}}}$.
Adding â€˜1â€™ on both sides, we get
\begin{align} & 1+y=1+\dfrac{1-{{x}^{4}}}{1+{{x}^{4}}} \\ & 1+y=\dfrac{(1+{{x}^{4}})+(1-{{x}^{4}})}{1+{{x}^{4}}} \\ & 1+y=\dfrac{2}{1+{{x}^{4}}}.........(iii) \\ \end{align}
Substituting equation (iii) in equation (ii), we get
\begin{align} & \dfrac{dx}{dy}=\dfrac{-1}{2{{x}^{3}}{{\left( \dfrac{2}{1+{{x}^{4}}} \right)}^{2}}} \\ & \Rightarrow \dfrac{dx}{dy}=\dfrac{-{{(1+{{x}^{4}})}^{2}}}{2{{x}^{3}}{{(2)}^{2}}} \\ & \dfrac{dx}{dy}=\dfrac{-{{(1+{{x}^{4}})}^{2}}}{8{{x}^{3}}}.........(iv) \\ \end{align}
Now multiplying equation (i) and (iv), we get
$\dfrac{dy}{dx}.\dfrac{dx}{dy}=\dfrac{-8{{x}^{3}}}{{{(1+{{x}^{4}})}^{2}}}.\dfrac{-{{(1+{{x}^{4}})}^{2}}}{8{{x}^{3}}}$
Cancelling the like terms, we get
$\dfrac{dy}{dx}.\dfrac{dx}{dy}=1$
Therefore, the correct answer is option (a).

Note: In this problem we can also directly get the answer by cancelling the like terms, i.e., $\dfrac{dy}{dx}.\dfrac{dx}{dy}=1$